Chosen Basic Legal and Organizational Aspects of Electronic Documents Archiving in Public Institutions - Wójtowicz, Radosław (Advanced Information Technologies for Management – AITM 2009, 2009)
The article presents chosen legal and organizational aspects of the archiving of electronic documents in public institutions in Poland. Section 2 of the study concentrates on the key terminology. Section 3 describes short profile of the most important legal acts. Section 4 of the article shows one exemplary organizational and technical solution for archival documents management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 216-224